Comparative analysis of jQuery Mobile library and Bootstrap framework in responsive websites development - Wrońska, Marta; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2016)
Article presents comparative analysis of jQuery Mobile library and Bootstrap framework in responsive site development. The comparative based on two websites, made in these technologies. Criterions of analysis are: compatibility of mobile devices, prepared components, loading speed on different devices, code size and compatibility with W3C and Google standards. Both technologies in a large degree helps in process of websites development, although jQuery Mobile is more expanded.